Chimeric Antigen Receptor T-Cell Therapy in Glioblastoma: Current and Future - Li, Long; Zhu, Xiqun; Qian, Yu; Yuan, Xiangling; Ding, Yi; Hu, Desheng; He, Xin; Wu, Yuan (Frontiers in Immunology, 2020)
Glioblastoma (GBM) is a highly aggressive glioma with an extremely poor prognosis after conventional treatment. Recent advances in immunotherapy offer hope for these patients with incurable GBM. Our present review aimed to provide an overview of immunotherapy for GBM, especially chimeric antigen receptor T-cell (CAR T) therapy. CAR T-cell immunotherapy, which involves the engineering of T cells to kill tumours by targeting cell surface-specific antigens, has been successful in eliminating B-cell leukaemia by targeting CD19. IL-13Rα2, EGFRvIII, and HER2-targeted CAR T cells have shown significant clinical efficacy and safety in phase 1 or 2 clinical trials conducted in patients with GBM; these findings support the need for further studies to examine if this therapy can ultimately benefit this patient group. However, local physical barriers, high tumour heterogeneity, and antigen escape make the use of CAR T therapy, as a treatment for GBM, challenging. The potential directions for improving the efficacy of CAR T in GBM are to combine the existing traditional therapies and the construction of multi-target CAR T cells.